أحكام اندماج الشركات في الفقه والقانون وأثرها على تطوير الصناعة المالية - عبد الوهاب عبد الله أحمد المعمري (مجلة الدراسات الاجتماعية, 2016)
The merger among the companies has become a common phenomenon in the contemporary economic life.  This phenomenon has different reasons, particularly among the large companies. This merger is one of the methods for forming large economic projects and a means of the formation of holding companies. It has become a point of economic, jurisprudential and legal interest.  Merger of the companies is a way towards changing the shape of the companies, increasing their capital and overcoming the difficulties that they may encounter. Merger of the companies is one of the forms of financial engineering and modern financial industry. The study aimed to investigate the provisions of the merger of companies in the Islamic jurisprudence and Yemeni law and find out jurisprudential and legal solutions for the problems that may arise during the merger of the business companies. It also aimed at identifying the impact of the merger of the business companies on the Islamic financial industry development. The study used the analytical comparative method to achieve the intended results and propose certain recommendations to the specialists and Islamic financial industry professionals. It employed practical applications in the jurisprudential authentication for merging companies. The results of the study revealed that the merger of companies has an impact on the development of the Islamic financial industry through developing and focusing on the economic activity of the merged companies. The merger provides technical and specialized expertise that contributes to the development and engineering of the Islamic finance industry. Additionally, it provides economic efficiency and Islamic credibility for the Islamic financial innovations along with a conducive environment for the financial innovation in the Islamic financial industry in light of the purposes of the Islamic law. The results indicate the need to encourage national companies to compete and increase their quality levels so that they can participate and interact with other companies in light of globalization. This interaction should be consistent with the principles of Islamic religion and never harm the interests of its citizens.